Operators on Sobolev Type Spaces (Communications in Mathematical Research, 2023)
In this paper, we introduce the work done on Hardy-Sobolev spacesand Fock-Sobolev spaces and their operators and operator algebras, including the study of boundedness, compactness, Fredholm property, index theory,spectrum and essential spectrum, norm and essential norm, Schatten-p classes,and the $C^∗$ algebras generated by them.